Impact of climatic conditions on photovoltaic modules performance - Mustapha DIDA; Slimane BOUGHALI; Djamel BECHKI1; Hamza BOUGUETTAIA (University of Eloued جامعة الوادي, 2019)
Significant advances have been made in PV systems within the last few decades. However, designers still face challenges related to the effects of climate conditions on PV systems performance. Climatic conditions such as temperature, humidity, wind velocity, solar irradiation and dust accumulation can effect significantly on the performance of PV modules. This experimental work aims to determine the effect of two parameters (PV module temperature and dust accumulation) on output power of solar PV panels in arid area. The experimental results showed the effect of dust accumulation in drooping of photovoltaic energy production, with decreasing by 5.35%, 0.38% and 5.94% in short circuit current, open circuit voltage and maximum power output respectively compared to cleaned PV panel. In the other hand results showed that the open circuit voltage and maximum power of non-cooled PV module are lower than cooled module by 5.64% and 6.35% respectively.
Intervention
Keywords: temperature; output power; dust accumulation; photovoltaic; cooling.